PENGARUH SUHU TERHADAP KONDUKTIVITAS BAHAN KOMPOSIT (AgI)0,3(p-Al203)0,7 DAN (AgI)0,5(B-Al203)0,5 - Purwanto, P.; Purnama, Safei (MESIN, 2007)
The composite materials of (Agl)ârffi-AliOj),,? and (Agl)â5(p-Al20})ll5 have been madebysolid state reaction mixing between Agl with /3-AI20j. The results show that the conductivity valuesof (AgOoJp-AliOj),,- were 5.98xW5 to 9.47xIO3 S/m, and the conductivity values of (Agl),l5(p-Al?Os),)j were 0.33x/04 to 4.47x/03 S/m asfunction of temperature. The conductivity of materialscompositedecreased at transition temperature, but the conductivity ofAgl increased with temperature.The activation energy of (Agl)o.}(/3-A/20})â- and (Agl)â5(P-Al203),,5 relative stable with value ofactivation energy between 0.74xl02" J to 2.80x102" J. The diffraction peaks of (Agl),, /fi-Al:Oj)â. -and(AgQojffi-dljOjJoj have thepeak ofAgl.